Educational Research Practice in Southern Contexts (Taylor & Francis, 2023)
Bringing together a unique collection of 18 insightful and innovative internationally focused articles, Educational Research Practice in Southern Contexts offers reflections, case studies, and critically, research methods and processes designed to decentre, reframe, and reimagine educational research in ways that question existing approaches and operationalise the tenets of decolonising theory.